Exploring the domain of accident law taking the facts seriously - Dewees, Donald N. 1941-; Duff, David 1959-; Trebilcock, Michael J. 1941- (Oxford University Press, 1996)
Most of the academic literature on the tort system has traditionally been doctrinal or, in recent years, highly theoretical. Very little of this literature provides an in-depth consideration of how the system works, and whether or not there are any feasible alternatives. Exploring the Domain of Accident Law contributes valuable new evidence to the tort law reform debate. It will be of interest to academic lawyers and economists, policy analysts, policy professionals in government and research organizations, and all those affected by tort law reform